Sistem Informasi Distribusi Obat Dan Alat Kesehatan Pada Apotek Kinibalu Banjarmasin - Ari Noor Wahyudi (Journal Information Technology Trends (JITRENDS), 2026)
Apotek Kinibalu Banjarmasin is a sole proprietorship engaged in pharmaceutical services as well as the distribution of medicines and medical devices. Previous distribution data management was still performed manually using ledgers and physical documents, leading to difficulties in retrieving transaction history, potential recording errors, the risk of lost archives, and delays in compiling inventory and financial reports. This research aims to design and build a web-based information system for the distribution of medicines and medical devices to support integrated data management. The software development method used is the Waterfall model, which encompasses requirements analysis, design, implementation, and testing. System modeling utilizes the Unified Modeling Language (UML), while the implementation relies on PHP, MySQL, HTML, CSS, JavaScript, and Apache. Functional testing was conducted using the Black-Box Testing method across 11 test classes covering login processes, master data management, distribution transactions, expenditure, and report generation. The test results indicate that all test classes yielded expected outputs in accordance with requirements. Furthermore, the system implementation helps accelerate distribution transactions and report generation compared to manual procedures. The developed system assists employees in centrally managing stock data, distribution transactions, customer receivables, and managerial reports.